Kajian Tentang Motivasi, Lingkungan Kerja Dan Disiplin Kerja dan Pengaruhnya terhadap Kinerja Karyawan - Putu Novi Andini; Ketut Listiani; Elas Fitriyani; Bakhtiar; Marsal (LPPM STIEM BONGAYA, 2024)
: In the era of competitive globalization, employee performance is one of the key factors for a company's success. Optimal performance can increase productivity, efficiency, and profitability of the Company. The study examines the effect of motivation, work environment and work discipline on employee performance. The purpose of this study was to determine how much influence the work environment, motivation and work discipline have on the performance of employees of PT Tunas Dwipa Matra Palopo City Branch. This research uses a quantitative method which involves 30 respondents who are employees of PT Tunas Dwipa Matra Palopo City Branch. From this study it was found that simultaneously the variables of motivation, work environment and work discipline have a significant effect on employee performance at PT Tunas Dwipa Matra, Palopo Branch. Partially, the motivation variable has a significant effect on employee performance at PT Tunas Dwipa Matra Palopo Branch. Partially, the work environment variable has no significant effect on employee performance at PT Tunas Dwipa Matra Palopo Branch. Partially, work discipline variable has a significant and positive effect on employee performance at PT Tunas Dwipa Matra Palopo Branch. The implication of this research is that employees must improve cooperation between employees, work effectiveness and help each other, besides that the company improves or improves the work atmosphere by creating an open and inclusive work environment. And finally, employees must be able to complete the assigned tasks on time and not delay their work